ADOPSI TEKNOLOGI SISTEM INFORMASI AKUNTANSI MELALUI PEMANFAATAN ZAHIR ACCOUNTING (STUDI KASUS : PT. ANEKA SISTIM INFORMASI BOGOR) - Eni Heni Hermaliani; Devy Narulyta (Jurnal Ilmiah SINUS, 2018)
PT. Aneka Sistem Informasi is a company engaged in trade and services, in which the process of processing and application of financial transaction data is still using conventional system. Through this research the authors describe the outline of accounting information using Zahir Accounting application. Accounting information system is a computer-based system that includes the transaction processing cycle, the use of information technology and information system development. The purpose of this research is to facilitate data entry transaction and financial reporting using accounting program applications. While the data collection method used is a direct observation of transactions that occur in the daily activities of business process activities, then do the interview on the Store Manager and Administration. The literature review studies complement two previous data collection techniques to strengthen theoretically. The result of data processing by using the application of accounting program starts from data entry by doing initial setup, beginning balance, master data up to transaction entry. Thus it will automatically generate the necessary financial statements to be more effective and efficient in making financial statements and facilitate the decision-making process.